Features of left ventricular remodeling in hypertension patients with comorbid gout - Daniuk, I. O.; Dotsenko, S. Ya.; Rekalov, D. G.; Chorna, I. V. (Zaporozhye Medical Journal, 2018)
Gout is the most common cause of inflammatory arthritis in men elder than 30 years. The association of gout with hypertension is up to 80 % of cases. Study of cardiovascular system remodeling is very relevant. Aim. To compare the left ventricle remodeling features in patients with hypertension combined with primary gout and patients with essential hypertension without disorders of purine metabolism. Materials and methods. 50 men with hypertension manifested on the gout background, 30 men with essential hypertension without disorders of purine metabolism and 20 healthy men were examined. The main parameters of left ventricle were determined using echocardioscopy. Results. The statistically significant increase in volumetric parameters of the left ventricle in patients with hypertension on the gout background in contrast to the comparison groups and significant decrease in ejection fraction as compared to healthy men were found. The significant increase in left ventricular mass, myocardial mass index and diastolic left ventricle dysfunction in patients with gout were revealed. Using the multivariate analysis of variance we determined an effect of hypertension degree, gout duration and abdominal obesity presence on the process of left ventricle remodeling. The increase in serum uric acid concentration correlated with an increase in left ventricular mass and myocardial mass index. The most of patients with hypertension and gout had the concentric left ventricular hypertrophy. Conclusions. Arterial hypertension on the gout background is characterized by a significant increase in left ventricular mass and myocardial mass index and the prevalence of concentric hypertrophy pattern of left ventricular geometric remodeling in comparison to patients with essential hypertension. Significant increase in myocardial stiffness and its diastolic dysfunction occurred in patients with hypertension on the gout background. Concentration of serum uric acid correlates with the increase in left ventricular mass and myocardial mass index.